Mexico: Enrollment Competition, Accreditation, and the Public-Private Market - Casillas, Juan (International Higher Education, 2013)
Accreditation is becoming a new battleground for public and private institutions in Mexico. Public and mid-profile private universities design marketing strategies based on the legitimation they get from accrediting agencies in order to lure and enroll students.